Association between postnatal maternal serology and congenital cytomegalovirus infection in neonates with jaundice - Puspa Wardhani; Joko Pamungkas; Dominicus Husada; Ernawati Ernawati; Nyilo Purnami; Munawaroh Fitriah; Reni Prasetyani (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2026)
Congenital cytomegalovirus (CMV) infection is one of the most prevalent infections at birth and can lead to severe health complications in neonates. Timely detection is crucial. However, polymerase chain reaction (PCR) testing is often unavailable in numerous healthcare settings. In such cases, maternal CMV antibody testing may assist in identifying at-risk infants. In the development of diagnostic methods to date, there is no single method for detecting CMV infection in pregnant women at all stages of pregnancy. This study examined the relationship between maternal CMV serology after delivery and congenital CMV infection in newborns presenting with symptoms including jaundice, prematurity, or low birth weight. Urine samples from neonates within the first 21 days of life were analyzed for CMV DNA via PCR, while maternal IgG and IgM antibodies were assessed within three weeks after delivery. A total of 87 neonates were examined, with 28 (32.2%) testing positive for CMV DNA. Neonatal jaundice was significantly associated with CMV infection, whereas prematurity and low birth weight were not. Maternal CMV IgM positivity was significantly correlated with neonatal CMV PCR positivity, while maternal IgG did not exhibit a significant relationship. In conclusion, maternal CMV IgM positivity post-delivery may assist in identifying newborns requiring confirmatory PCR testing, particularly in healthcare environments with constrained diagnostic resources.